Neurobiology, Pathophysiology, and Treatment of Melatonin Deficiency and Dysfunction - Rüdiger Hardeland (The Scientific World Journal)
Melatonin is a highly pleiotropic signaling molecule, which is released as a hormone of the pineal gland predominantly during night. Melatonin secretion decreases during aging. Reduced melatonin levels are also observed in various diseases, such as types of dementia, some mood disorders, severe pain, cancer, and diabetes type 2. Melatonin dysfunction is frequently related to deviations in amplitudes, phasing, and coupling of circadian rhythms. Gene polymorphisms of melatonin receptors and circadian oscillator proteins bear risks for several of the diseases mentioned. A common symptom of insufficient melatonin signaling is sleep disturbances. It is necessary to distinguish between symptoms that are curable by short melatonergic actions and others that require extended actions during night. Melatonin immediate release is already effective, at moderate doses, for reducing difficulties of falling asleep or improving symptoms associated with poorly coupled circadian rhythms, including seasonal affective and bipolar disorders. For purposes of a replacement therapy based on longer-lasting melatonergic actions, melatonin prolonged release and synthetic agonists have been developed. Therapies with melatonin or synthetic melatonergic drugs have to consider that these agents do not only act on the SCN, but also on numerous organs and cells in which melatonin receptors are also expressed.